Improving Literacy and Numeracy in Natural Primary Schools Campus Teaching Program: SRL - Rolius Telaumbanua; Alit Rahmat; Riswan Zega (Eduvest - Journal of Universal Studies, 2024)
The Teaching Campus Program is an important initiative to improve the literacy and numeracy skills of elementary school students in Indonesia. The aim of this research is to evaluate the effectiveness of these programs in achieving their goals using the Systematic Literature Review (SLR) method. Of the seven articles analyzed starting from campus programs teaching classes 1, 2, 3, 4, 5 and 6, it was found that these programs succeeded in increasing students' interest in learning, reading, writing and numeracy skills, as well as strengthening their personality and social skills. A holistic approach that includes the use of technology and community involvement has proven effective in creating a supportive learning environment. However, challenges such as program consistency and resource support must be addressed to ensure long-term sustainability. Therefore, these programs have great potential to improve the quality of basic education in Indonesia, but further efforts are needed to maximize their impact.